Spatial variability of rainfall erosive potential in Alagoas - Silva , Thaís Rayane Gomes da (2023)
Erosion, characterized by the erosion of the soil due to the removal of surface layers caused by the action of erosive agents, is one of the main problems of Brazilian soils, thus generating an environmental, social and economic impact. In this way, the objective of this research was to determine the erosivity factor through rainfall data from the municipality of Santana do Ipanema, located in the hinterland of Alagoas, in the observation period from 1912 to 1985. These data were tabulated to calculate rainfall, rainfall coefficient and its relation to erosivity using six methods. During the 73-year period of data analysis, the annual average attainment was 851.96 mm. During this observation period, it was found that of the total, 27 years registered values above the average, while 46 years presented values below the historical average, with the wettest months being May, June and July, presenting values above the average. The average annual erosivity calculates using the six mathematical models values ranging from 500 to 7600 MJ mm ha-1 h-1 year-1 for a study area. All models can be used as an alternative to determine the average monthly and annual rainfall erosivity for the municipality of Santana do Ipanema in Alagoas.